Contaminants of Nasiriyah thermal power station and its impact on the Euphrates River in Thi Qar city - A.G.; A.Y.Makah; R.A.Ali (University of Thi-Qar Journal, 2020)
The research included the study of environmental pollution in the Euphrates River in the vicinity of the power plant in Thi Qar city and its impact on the quality and environment of the river water. The study showed the high values ??of most physical and chemical properties in the river water, which confirms the effect of the electric station. The samples were taken during the months of February and April of 2019. Six stations were chosen along the river in the study area, two stations before the electric station and two stations next to the station and two stations after the electrical station. The samples were taken from the edge of the river and from the middle and at a depth of (30) cm. The laboratory tests were conducted to calculate the electrical conductivity ,PH and the calcium and magnesium ion rates. The study of properties showed that all levels except PH are not in accordance with the Iraqi and global determinants of potable water as shown in Table (2). We also noticed that these rates were higher in February than in April due to the rain that swept the country and consequently the rise in the water level of the river, which led to a decrease in the percentage of pollutants.